Pathways for scaling solar-based irrigation technology ownership in Nigeria: suitability and key stakeholder mapping in Kebbi, Kano, and Kaduna states - Ojeleye, O. A.; Oke, Adebayo; Tilahun, Seifu A.; Minh, Thai Thi (International Water Management Institute, 2025)
Northern Nigeria’s floodplains offer significant potential for solar-based irrigation systems (SPIS) due to abundant solar resources and shallow groundwater. Despite this opportunity, adoption remains low, as farmers continue relying on costly fuel-powered pumps. The recent removal of fuel subsidies in Nigeria has intensified financial challenges, increasing interest in solar alternatives. Yet, high upfront costs, weak supply chains, and limited technical support continue to hinder uptake of SPIS. This report, developed under CGIAR’s Scaling for Impact Science programme, aims to co-design scalable SPIS pathways by engaging stakeholders and addressing systemic constraints.